Re-sequencing of candidate genes FOXF1, HSPA6, HAAO, and KYNU in 522 individuals with VATER/VACTERL, VACTER/VACTERL-like association, and isolated anorectal malformation - Thiem, Corina E.; Stegmann, Jil D.; Hilger, Alina C.; Waffenschmidt, Lea; Bendixen, Charlotte; Köllges, Ricarda; Schmiedeke, Eberhard; Schäfer, Frank Mattias; Lacher, Martin; Kosch, Ferdinand; Grasshoff-Derr, Sabine; Kabs, Carmen; et al. (Birth Defects Research, 2022)
Background: The acronym VATER/VACTERL association describes the combination of at least three component features (CFs): vertebral defects (V), anorectal malformations (ARM) (A), cardiac defects (C), tracheoesophageal fistula with or without esophageal atresia (TE), renal malformations (R), and limb defects (L). Individuals presenting two CFs have been termed VATER/VACTERL-like. Recently, FOXF1, HSPA6, HAAO, KYNU, TRAP1, and ZIC3 have been proposed as candidate genes for VATER/VACTERL, VATER/VACTERL-like, and ARM. Re-sequencing studies identified disease-causing variants in TRAP1 and ZIC3, the contribution of other genes was not independently investigated. One affected variant carrier in FOXF1 was previously identified. Here we re-sequenced FOXF1, HSPA6, HAAO, and KYNU in 522 affected individuals. Methods: Using molecular inversion probe (MIP) technology, re-sequencing was performed in 63 individuals with VATER/VACTERL association, 313 with VATER/VACTERL-like association, and 146 with ARM. All individuals were of European ethnicity. Variant filtering considered variants with a minor allele frequency (MAF) ≤0.01 for putative recessive disease-genes HSPA6, HAAO, and KYNU. For the putative dominant disease-gene FOXF1 we considered variants with a MAF ≤0.0001. In silico prediction tools were used for further prioritization. Results: Only two variants in FOXF1 in two independently affected individuals [c.443G>T, p.(Cys148Phe); c.850T>C, p.(Tyr284His)] passed our filter criteria. One individual presented with ARM, the second presented with TE and C comprising atrial and ventricular septal defects. Sanger sequencing confirmed both variants but also their inheritance from the healthy mother. Conclusion: Our analysis suggests that FOXF1, HSPA6, HAAO and KYNU do not play a major role in the formation of VACTER/VACTERL phenotypes or ARM.
CRIS-Team Scopus Importer:2022-04-15
Keywords: anorectal malformation; birth defects; candidate gene; penetrance; variants